Description of a new codling species of Physiculus from Taiwan (Gadiformes: Moridae) - Tang, Chi-Ngai (Zootaxa, 2021)
A new species of codling Physiculus megastomus sp. nov. is described based on the holotype and a subadult paratype collected from northern and eastern Taiwan. The new species is classified in Physiculus by the presence of a ventral light organ on the abdomen and a chin barbel, and the absence of vomerine teeth. It is distinguished from congeners in having a large mouth with the posterior end of the maxilla extending well behind the level of the posterior margin of the orbit, its length 57.8‒60.7% in head length (HL) and the combination of the following characters: both jaws bearing caniniform teeth; snout, suborbital area, and gular region fully scaled; ventral light organ small, its length 5.5‒6.7% of distance from the interventral line to the origin of the anal fin (InV-af), located approximately at the mid-point of InV-af; five gill rakers on the upper limb of the first gill arch. DNA barcoding supported the establishment of the new species.